Novels Ancika Dia Yang Bersamaku Tahun 1995 by Pidi Baiq in Feminist Perspective - Iqbalva Demas Wibowo; Onok Yayang Pamungkas (CV. Media Digital Publikasi Indonesia, 2023)
This study represents an effort to investigate the feminist spirit within Pidi Baiq's novel